Penilaian Wisatawan Terhadap Komponen Destinasi Wisata: Atraksi, Amenitas, Aksesibilitas dan Pelayanan Tambahan Pada Objek Wisata Kebun Raya Liwa - Machya K. Tsani; Sugeng P. Harianto; Trio Santoso; Niskan W. Masruri; Gunardi D. Winarno (Fakultas Kehutanan Universitas Gadjah Mada, 2021)
The development of a tourist attraction must pay attention to the tourists’necessity. To fulfill these needs there are 4 main components that must be fulfilled. This study aims to determine the assessment of tourists to the 4 main components (attraction, amenities, accessibility, and ancillary service) on the natural attractions of the Liwa Botanical Garden. This research was carried out in the Liwa Botanical Garden located in Kubu Perahu Village, Balik Bukit District, Liwa City, West Lampung Regency. Data was collected for 100 tourists by accidental sampling. Data analysis using a likert scale and data scoring. The results showed that of the 4 components of tourist destinations in the KRL object, only the attraction component had adequate value. The three other components (accessibility, safety and ancillary services) are in the sufficient category so that it would be better if there were improvements to the indicators of the 3 other variables such as: addition of public transportation, control of parking areas, addition of food stalls, procurement of lodging for public, improvement of central services information, the addition of public toilets, provided a special place to buy souvenirs, giving pictures of the types of rubbish in the trash, and need to add a communication network spot so that tourists feel more comfortable and enjoy their visit.